Somatic determinants of changes in selected body posture parameters in younger school-age children - Labecka,Marta Kinga; Górniak,Krystyna; Lichota,Małgorzata (PeerJ, 2021)
Background The aim of this study was to describe changes in selected parameters of body posture in children between 5 and 9 years old with diversified somatic structures. Methods The study was carried out in 2015 and then repeated in 2018 among 67 participants who had previously been observed to have scoliotic posture. Basic body weight and height measurements were taken, which were then used to calculate the body mass index. Posture tests were conducted using the photogrammetric method. Results Girls and boys were not significantly different in body dimensions. With age, the number of overweight boys and children with normal growth-weight proportions increased. Temporary differences in posture variables indicating abnormalities were small. Conclusions There were no significant differences in somatic parameters between the girls and the boys. Those children with a slender body structure had the most abnormalities in the coronal plane. On the other hand, changes in spinal position in the sagittal plane were more frequent in overweight children. Relations were noted between the compensation index in the sagittal plane and deviation of the trunk inclination, the maximum deviation of the line of the spinous processes, and the angle of the shoulder line in the coronal plane and body mass index values were noted.
Keywords: Body posture; Somatic parameters; Changes; Children; Photogrammetric method